Idiopathic digital clubbing with palmo-plantar pachydermia and hyperhidrosis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2014)
Digital clubbing can be (3) acquired and secondary to lung cancer, cyanogenic congenital heart disease, infections (lung, endocarditis), chronic inflammation of various organs (inflammatory bowel disease, chronic hepatitis, thyroiditis, LES), hypertrophic osteoarthropathy. In these cases, in order to explain the deformation of distal phalanges you can assume a blood hyperflow linked to the prevalence of vasodilator factors or to tissue hypoxia. Beside the secondary forms there are congenital forms present from the first periods of life, influenced by genetic factors. Pachydermia and palmoplantar hyperhidrosis are signs of pachydermoperiostosis (1, 2), a syndrome characterized by congenital hypertrophy of the skin and the bones of the extremities as well as digital clubbing. Our patient, who do not currently presents bone lesions, should be monitored for the possible occurrence of these changes in the future.